GABAergic regulation of striatal spiny projection neurons depends upon their activity state. - Michelle Day; Marziyeh Belal; William C Surmeier; Alexandria Melendez; David Wokosin; Tatiana Tkatch; Vernon R J Clarke; D James Surmeier (PLoS Biology)
Synaptic transmission mediated by GABAA receptors (GABAARs) in adult, principal striatal spiny projection neurons (SPNs) can suppress ongoing spiking, but its effect on synaptic integration at subthreshold membrane potentials is less well characterized, particularly those near the resting down-state. To fill this gap, a combination of molecular, optogenetic, optical, and electrophysiological approaches were used to study SPNs in mouse ex vivo brain slices, and computational tools were used to model somatodendritic synaptic integration. In perforated patch recordings, activation of GABAARs, either by uncaging of GABA or by optogenetic stimulation of GABAergic synapses, evoked currents with a reversal potential near -60 mV in both juvenile and adult SPNs. Transcriptomic analysis and pharmacological work suggested that this relatively positive GABAAR reversal potential was not attributable to NKCC1 expression, but rather to HCO3- permeability. Regardless, from down-state potentials, optogenetic activation of dendritic GABAergic synapses depolarized SPNs. This GABAAR-mediated depolarization summed with trailing ionotropic glutamate receptor (iGluR) stimulation, promoting dendritic spikes and increasing somatic depolarization. Simulations revealed that a diffuse dendritic GABAergic input to SPNs effectively enhanced the response to dendritic iGluR signaling and promoted dendritic spikes. Taken together, our results demonstrate that GABAARs can work in concert with iGluRs to excite adult SPNs when they are in the resting down-state, suggesting that their inhibitory role is limited to brief periods near spike threshold. This state-dependence calls for a reformulation for the role of intrastriatal GABAergic circuits.